A case with acute-on-chronic liver failure receiving liver transplantation during daclatasvir and asunaprevir therapy in chronic hepatitis C patient. (30th April 2018) - Park, Wonhyeong; Jung, Jihwan; Yang, Soo Hyun; Lee, Danbi; Kang, Hyo Jeong
Abstract: We report a case with hepatitis C virus genotype 1 b liver cirrhosis who received liver transplantation because of acute-on-chronic liver failure during daclatasvir (DSV) and asunaprevir (ASV) combination therapy. To our knowledge, this is the first case received liver transplantation during DSV + ASV therapy. Therefore, clinicians should pay particular attention to the possibility of acute liver failure during DSV and ASV combination therapy.